CALCULATION OF SHAPE AND DIMENTIONS OF SEMIPRODUCTS IN PROCESSES OF DIE FORGING USING OF INVERSE TASKS OF THE METALFORMING - A.V. Vovchenko; Yu.N. Reznikov (Вестник Донского государственного технического университета, 2018)
The outcomes of rational design of semiproducts in process of die forging for the forging of the hemispherical shape are submitted. The approach is realized by a boundary-element solution of a sequence of inverse tasks of metal flow when filling the die cavity on algorithm reverse loading. The obtained solution allows to realize a flawless die forging process at the minimum accepted size of a burr.